Influence of Artocarpus communis Leave Extract on the Physical Characteristic of Pellet - Heni Rachmawati; Tjandrawati Mozef; Shafiqah Adam (Institut Teknologi Bandung, 2010)
Artocarpus communis (Forst.) is popularly known in English as breadfruit tree because of the bread-like texture of its edible fruits. The leaves are potential for fever and liver disorders and it also possesses significant anti-platelet and anti-inflammatory activities. The aim of this study is to formulate ethyl acetate extract of Artocarpus communis leaves into a solid dosage form. Pelletization was developed to formulate the extract. The formula was prepared using various ratios of extract (5, 10, 15 and 20 %) with PVP as a binder and Avicel pH101 as a filler. The influence of extract concentration was studied on the pellet characteristics. Pellet was prepared by extrusion-spheronization technique. In order to produce pellet with optimum diameter (500-900 Âµm), the moisture of the extrudates must be around 40%, with spheronizer speed of 800-900 rpm for 1.5 minutes. In particular for flow property, all pellets containing more than 5% of Artocarpus communis leaf extract were better (> 8 g/s) over blank pellets (< 4 g/s). In conclusion, the presence of extract in the pellet formulas improved the physical characteristic of pellet. The self binding property of the extract is suggested as a key parameter for this improvement.